Radiommunoassays for the 70,000-molecular-weight glycoproteins of endogenous mouse type C viruses: viral antigen expression in normal mouse tissues and sera. - Hino, S (1976)
Genetic information coding for type C RNA viruses is transmitted within the DNA of mouse cells. At least three endogenous viruses have so far been immunologically distinguished by radioimmunoassays for their 12,000-molecular-weight polypeptides (p12). In the present study, the 70,000-molecular-weight glycoproteins (gp70) of three prototype viruses were purified, and competition radioimmunoassays were developed for each. By use of these immunoassays, the antigenic determinants of gp70's of different classes of endogenous virus, isolated from the same and from a variety of other mouse strains, were readily discriminated. In contrast, viruses of the same class were indistinguishable. These findings further document the existence of three distinct endogenous viruses of mouse cell. The levels of type C viral gp70 were quantitated in tissues and sera of several inbred strains. The pattern of immunological reactivity of the gp70 detected in serum was indistinguishable from that of the viral gp70 partially purified from tissues of the same strain. Moreover, in each case it was indistinguishable from that of a specific class of endogenous virus. In virus-negative tissues of BALB/c and NIH Swiss mice, the viral gp70 detected was shown to be representative of a class III endogenous virus whose p12 polypeptide was also expressed by the same cells.